The Effect of Live Tiktok Shop Bundle Promotion on Repeat Purchases of The Originote Products - Annisa Firdaus Fahmayanti; Avira Budianita; Darsin (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2026)
This study aims analyze the effect of live Tiktok Shop bundle promotions on repeat purchase of The Originote skincare products. this research uses a quantitative with a survey method. the population in this study were students of MA Muwahidun Pati who had puschased the Originote products trough live TikTok Shop promotions. Data were collected through online questionnaires distributed to 87 respondents using a purposive sampling technique. Data analysis was conducted using Structural Equation modeling with Partial Least Square (SEM-PLS). The result show that live TikTok Shop bundle promotions have a positive and significant effect on repeat purchase. This indicates that attractive bundle pricing, time-limited promotions, and interactive live streaming can increase customer satisfaction and encourage repeat purchase behavior. in addition, the findings highlight the importance of live commerce strategies in building costumer engagement and trust. Therefore, businesses are recommended to optimize promotional strategies through live streaming to enhance customer loyalty and long-term purchasing behavior.